The Udder Side of Maritime Rights: Bovine Tuberculosis and Federal Regulatory Power in 1920s Prince Edward Island - Jenkins, Jane (Acadiensis, 2011)
This article traces the federal program to eradicate bovine tuberculosis during the early 20th century, the dynamics of Prince Edward Island’s two-year battle to participate, and the motivation behind the unexpected decision to test PEI cows after steadfast refusals. Rather than a progress narrative, the article reveals the rise of the regulatory state in tandem with the authority of veterinary science – wielded in order to fracture the unity of regional dissent. The establishment of PEI as a zone free of bovine tuberculosis was thus as much about politics and profit as it was about public health and progressivism. Résumé Le présent article retrace l’évolution du programme fédéral d’éradication de la tuberculose bovine au début du 20e siècle, la dynamique de la bataille que l’Île-du-Prince-Édouard livra pendant deux ans pour y participer et les motifs à l’origine de la décision inattendue du gouvernement fédéral de tester les vaches de l’Île-du-Prince-Édouard après plusieurs refus catégoriques. Au lieu de faire le récit des progrès accomplis, l’article révèle la montée de la réglementation de l’État, de concert avec l’autorité des sciences vétérinaires, exercée pour briser l’unité de la dissidence régionale. Par conséquent, la désignation de l’Î.-P.-É. comme zone exempte de tuberculose bovine était autant une affaire de politique et de profit, qu’une question de santé publique et de progressivisme.